Wireless Local Area Network Security through Protocol Wireless Protected Access - Kumajas, Sondy; Sasukul, Julius; Siwi, Alexander; Saruan, Hellena (International Journal of Information Technology and Education, 2022)
This study discusses the security analysis of Wireless Local Area Network (Wireless LAN) in the Community against external attacks on the Wireless Protected Access (WPA), Web Proxy, and Virtual Private Network (VPN) protocols, used to attack LAN. Three types of software are used as attackers, namely, Network Stumbler, Aircrack and Wireshark attackers. The software is used on the laptop at a distance of 5m to 25m from the Wireless LAN access point. From the experimental results, it can be seen that the fastest response time by the WPA Protocol was given by the Network Stumbler attacker, followed by Aircrack and Wireshark.